O SENADO ROMANO E A CORTE IMPERIAL NO BAIXO IMPÉRIO: UMA REVISÃO - Machado, Carlos Augusto Ribeiro (PHOÎNIX, 2020)
In this article we intend to discuss some of lhe trends on the historiography on Late Roman politics. Basically, we shall be looking for the place ancient historians have assigned for the imperial court and the senate of Rome. There is a wide range of approaches, and we believe that re-reading and summarising these may be an important tool for those interested on this subject.